Debt Payment by Heir: A Study of Indonesian Legislation - Baso, Fatihani; Novita Mudriani Djaoe, Andi; Kholifah, Ayu; Kurniawan, Shelly; ., Puspasari (KnE Social Sciences, 2022)
The application of the Personality Principle in Article 1315 BW jo. 1240 BW in relation to Article 833 paragraph (1) BW was examined in this study, as well as whether these articles conflict with one another. Data were collected through interviews with key informants, and from legislation, journals, books and articles from websites. The study found that Article 833 paragraph (1) does not conflict with the Personality Principle because if the debtor dies, the heirs have no obligation to pay off the debtor’s debt, because an agreement only binds the parties who signed it, including the debt agreement. The bank would not declare the debt paid off until the insurance claim was settled. Keywords: debt payment, principle of personality, agreement